Millimeter wave antennas for 5G mobile terminals and base stations - Koul, Shiban K.; Karthikeya, G. S. (Boca Raton, FL : CRC Press, 2021)
This book discusses antenna designs for handheld devices as well as base stations. The book serves as a reference and a handy guide for graduate students and PhD students involved in the field of millimeter wave antenna design. It also gives insights to designers and practicing engineers who are actively engaged in design of antennas for future 5G devices. It offers an in-depth study, performance analysis and extensive characterization of novel antennas for 5G applications. The reader will learn about basic design methodology and techniques to develop antennas for 5G applications including concepts of path loss compensation, co-design of commercial 4G antennas with millimeter wave 5G antennas and antennas used in phase array and pattern diversity modules. Practical examples included in the book will help readers to build high performance antennas for 5G subsystems/systems using low cost technology. Key Features Provides simple design methodology of different antennas for handheld devices as well as base stations for 5G applications. Concept of path loss compensation introduced. Co-design of commercial 4G antennas with millimetre wave 5G antennas presented.Comparison of phased array versus pattern diversity modules discussed in detail.Fabrication and Measurement challenges at mmWaves and Research Avenues in antenna designs for 5G and beyond presented. Shiban Kishen Koul is an emeritus professor at the Centre for Applied Research in Electronics at the Indian Institute of Technology Delhi. He served as the chairman of Astra Microwave Products Limited, Hyderabad from 2009-2018. He is a Life Fellow of the Institution of Electrical and Electronics Engineering (IEEE), USA, a Fellow of the Indian National Academy of Engineering (INAE), and a Fellow of the Institution of Electronics and Telecommunication Engineers (IETE). Karthikeya G S worked as an assistant professor in Visvesvaraya technological university from 2013 to 2016 and completed his PhD from the Centre for Applied Research in Electronics at the Indian Institute of Technology Delhi in Dec.2019. He is a member of IEEE-Antenna Propagation Society and Antenna Test and Measurement society.
OCLC-licensed vendor bibliographic record.
Keywords: Antennas (Electronics) -- Design and construction; Millimeter wave devices; Mobile communication systems; COMPUTERS / Networking / General